The Corruption Behavior in The Behind of Fatsun Leadership of Kiai in The Region of Madura, Indonesia - Nadir Nadir; Win Yuli Wardani (Rechtsidee, 2019)
New corruption of the autonomous regions take a place, so that the government is unable to control the regional government. This is because the lack of supervision in the area during this is becoming the main factors a trigger regional heads to conduct corruption, and abuse of authority behind legitimacy leadership kiai. In addition, people in the they felt unable to be afraid to monitor and regional leaders, because it is still of cling values trach kiai. Hence, regional head lost his control. Local government administration as the base behavior corruption behind legitimacy leadership kiai because some respects, namely: (1) of the lack of supervision of the central government towards the regional government. (2) the the breadth of affairs which is the authority of the regional government. (3) of religiousness loss of values in self leader. (4) the weak regulation criminal sanctions for investors. (5) the lack of supervision of the society to the regional government. (6) values still a cling obedience the community against the figure of kiai. While the supporters become factors behavior corruption increasingly exist in perspective regional government reversed legitimacy leadership kiai, namely: (1) an opportunity patient office / erceived opportunity. (2) desire or the will to do corruption. (3) living expenses as pressure (lavish lifestyle as a necessity / living beyond one' s means, polygamy as a cost not light, promising welfare, promising removal of civil servants for temporary, promising free health.